Diálogos transnacionales entre los saberes técnicos e institucionales en la legislación sobre accidentes de trabajo, primera mitad del siglo XX - Ramacciotti, Karina (2015)
In the early twentieth century, Argentina began legislating occupational safety. Law no.9.688 legislated accidents in the workplace (1915) and granted legal jurisdiction to work-related problems. The approval of this legislation was in dialogue with proposals being produced in other regions. The links established between local figures and colleagues elsewhere are useful for examining the circulation, reception and legitimation of knowledge on a regional scale. The objective of this article is to examine the transnational references in local discussions about occupational accidents in Peru and Chile during the first half of the twentieth century.